The Pattern of the Formation and Role Playing of the Deep State in Turkey - Reza Razeghi (Dulat/pizhūhī, 2020)
This article analyzes the role and power of the military in Turkey and how they interfere in Turkey's political arena, using deep-state theory. The research question is that with regard to the Turkish constitutional amendments and the reduction of military influence on political affairs, is it possible for the country's military to become an active actor in the political arena? The conceptual framework of research is the theory of deep state. The research findings indicate that the military still has the potential for political participation and intervention in Turkish affairs, but for reasons such as reducing legitimacy, foreign pressure and a new understanding of security issues in Turkey, the military has found that Political issues should be solved by the government, not the military and the army headquarters. On this base, they have implicitly entered the coalition with Erdogan and the AKP because of their common enemies with the AK PARTy, including the Pkk and the Gulen Movement, and given that Erdogan's National security and fight against internal and external enemies need military support, and the army will cooperate with the AKP government if they consider national security and defense issues in their regard. The data collection method is document and library and data analysis is done by process tracking analysis.